Effect of rice (Oryza sativa) establishment methods and levels of irrigation and phosphorus on P use efficiency of zero-tillage maize (Zea mays) under rice based cropping system - SREELATHA, D; RAJU, M S; REDDY, M D; JAYASREE, G; REDDY, D V V (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted during two consecutive seasons of kharif and rabi of 2007-08 and 2008-09 atÂ College farm, College of Agriculture, Rajendranagar, Hyderabad on sandy clay loam soil. The experiment was laid out in split-plot design replicated four times. During kharif, the experimental field was divided into two blocks in each replication wherein two methods of rice crop establishment (Transplanted and Aerobic method) were evaluated. During rabi, zero-tilled maize was grown in sequence to rice while considering the two previous rice (Oryza sativa L.) crop establishment methods as main-plot treatments and two levels of irrigation (1.0 and 0.8 IW:CPE) and four levels of phosphorus (0,30,60 and 90 kg P2O5/ha) as sub-plot treatments. The objective of the study was to evaluate the effect of rice crop establishment methods, levels of irrigation and phosphorus on P nutrition of zero-tilled maize (Zea mays L.) under rice-maize system. The grain yield of maize improved significantly from 0 to 60 kg P2O5/ha application. Higher P-use efficiency was recorded in maize crop grown after transplanted rice than that of aerobic rice and the irrigations scheduled at IW: CPE ratio of 1.0 than with IW: CPE ratio of 0.8 during both the years. There was significant decrease in P- use efficiency with increase in P2O5 levels from 30 to 60 and 90 kg/ha (53.91 to 24.95 and 57.17 to 25.61 kg grain/kg P2O5/ha during 2007-08 and 2008-09 respectively). The balance sheet of available soil P at the end of two years in rice-maize crop sequence indicated that, the uptake of P by maize crop was much higher than the rice crop and the depletion of available soil P was maximum when phosphorus was applied to rice during kharif and without phosphorus application to maize during subsequent rabi. However, maximum accumulation of phosphorus was noticed when two crops were fertilized with 60 kg P2O5/ha for both rice and maize. Based on the yield-input relationship, the optimum level of phosphorus was 85.4 kg P2O5/ha for realizing higher yield of 7 309 kg/ha.